The Baobab (Adansonia digitata L.) in Southern Kenya–A Study on Status, Distribution, Use and Importance in Taita–Taveta County - Fischer, S.; Jäckering, L.; Kehlenbeck, K. (Springer, 2020)
Baobab (Adansonia digitata L.) is a multipurpose, drought resistant, wild fruit tree, endemic to arid and semi-arid lands of Sub-Saharan Africa. Baobab populations have been showing a lack of regeneration, and therefore causes concern for the species survival. This study investigated the state, distribution and use of baobabs in an under-researched population in Kenya, to identify the potential for further use and development of baobab resources. A baobab population was chosen in Taita–Taveta County, covering a sample area of 2015 km2. A systematic stratified transect survey was done to map baobab distribution using 49 transects (0.5 × 3 km each). The diameter at breast height and other indicators were measured on all baobabs in the transects to assess population status and health. A household survey (n = 46) and focus group discussions (n = 12) were done following the transect survey to gain an idea on the uses and distribution of baobab. In total, 432 baobab trees were measured and recorded in the research area of 2015 km2. The baobabs grew in two clusters (i.e., areas with a baobab density of ≥0.08 baobabs/ha). Both clusters showed rejuvenating populations. The main factors identified by the respondents, positively and negatively influencing baobab distribution were environmental factors, wildlife, human impact and commercial value. The study area shows a great potential for baobab to become an important part of the diet, due to its current use as an emergency food during food scarce times, and the relatively healthy and stable rejuvenating populations.